2020
DOI: 10.4103/ijpvm.ijpvm_229_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of acarbose on weight and metabolic, inflammatory, and cardiovascular markers in patients with obesity and overweight

Abstract: Background: Metabolic syndrome (MetS) refers to a cluster of risk factors for cardiovascular disease and type 2 diabetes. The aim of this study is to assess the effects of acarbose as an antihyperglycemic agent (drug) on late complications of MetS. Methods: This double-blind randomized clinical trial was done on patients with MetS admitted to Isfahan Endocrine and Metabolism Research Center. They were assigned randomly to two groups: A who received acarbose ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A post hoc analysis showed that weight loss with acarbose therapy was not based on glycemic control status, but relied on baseline body weight [ 147 ]. Acarbose significantly reduces body weight and abdominal obesity, decreases epicardial fat, intima-media thickness, C-reactive protein levels, and improves HDL (high-density lipoprotein) levels in patients with metabolic syndrome [ 148 ]. Acarbose decreased key markers (Iba1 + microglia, tumor necrosis factor-α, and glial fibrillary acidic protein) of hypothalamic inflammation, while long-term treatment of acarbose (from 3 to 9 months, 20 mg/kg/day) enhanced memory during aging in SAMP8 mice [ 149 , 150 ].…”
Section: Drugs With Antiaging Effectsmentioning
confidence: 99%
“…A post hoc analysis showed that weight loss with acarbose therapy was not based on glycemic control status, but relied on baseline body weight [ 147 ]. Acarbose significantly reduces body weight and abdominal obesity, decreases epicardial fat, intima-media thickness, C-reactive protein levels, and improves HDL (high-density lipoprotein) levels in patients with metabolic syndrome [ 148 ]. Acarbose decreased key markers (Iba1 + microglia, tumor necrosis factor-α, and glial fibrillary acidic protein) of hypothalamic inflammation, while long-term treatment of acarbose (from 3 to 9 months, 20 mg/kg/day) enhanced memory during aging in SAMP8 mice [ 149 , 150 ].…”
Section: Drugs With Antiaging Effectsmentioning
confidence: 99%
“…In individuals with T2DM, there is often an increase in inflammatory markers. Acarbose may decrease insulin resistance by reducing these inflammatory markers (Derosa & Maffioli, 2012;Khalili & Safavipour, 2020). Also, in the subgroup analysis, our results showed that only health status significantly affects the insulin level, however, it was shown that only the BMI has a significant effect on the HOMA-IR levels.…”
Section: Discussionmentioning
confidence: 51%
“…Some monoterpenes have been described as presenting antimicrobial properties and painkilling effects [ 25 ]. Another compound detected was acarbose, an alpha-glucosidase inhibitor, which is described as a group of poorly absorbed antidiabetic agents [ 26 ]. Finally, domains related to the production of antibiotics, such as ansamycins, enediyne, vancomycin, streptomycin, and validamycin, were also present.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they have also been associated with various antimicrobial, hypotensive, anti-inflammatory, and antipruritic functions, among others [ 48 ]. Of the antidiabetic drugs, acarbose is associated with lesser gastrointestinal side effects than other alpha-glucosidase inhibitors and has been used as a single drug or in combination with other antidiabetic medications to control blood glucose levels in type 2 diabetic patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%